Visual Movements and Sports Performance of the Tennis Player: Scoping Review - Pirachican Alaguna, Miguel Alfredo (2024)
Purpose: The presente study aims to explore the existing bibliography on visual skills and visual movements in tennis players. Method: We searched the Scopus, SPORTDiscus, PubMed and Google Scholar databases, which allowed us to select 37 empirical studies carried out with a quantitative method. The choice of the studies responded to the criteria established around the Keywords, the subject of the study and the research methodology. Results: The results are organized into three central topics: (a) Antecedents of visual skills in the 20th century, (b) 21st century: Role of saccadic movements, and (c) Reflections on the tennis feat and saccadic movements. Conclusions: Throughout several decades of research and monitoring of the “vision and sport” approach in field tennis, specifically in the visual movements between fixations and saccadic movements, differential levels of tennis performance can be identified with the potential to be indicators of better sports performance. Given that the tools used so far in this discipline for the selection and/or evaluation processes are not determinant, due to being a multifactorial sport discipline of perceptual-motor order and open skills, it is suggested that visual skills may be essential for the acquisition of a high competitive level. This aspect raises an interesting line of research that deserves further exploration in the future.